Manajemen Komunikasi Dakwah DKM Ummul Mukminin dalam Program Kajian Kemuslimahan - Dea Amanda Nabila; Kamil, Parihat; Suhendi, Hendi (UNISBA Press, 2024)
Abstract. Ummul Mukminin Mosque is a mosque located in the Bandung Islamic University area. Campus mosques have a very important role in life, through various structured programs and activities, campus mosques can become a place for students to increase their faith, as is done at the Ummul Mukminin Mosque through the Islamic studies program. However, not many female students take Islamic study programs. This research aims to find out how the communication management of DKM Ummul Mukminin's da'wah is implemented in the Muslimah study program, starting from planning, implementation, evaluation and corrective action for DKM Ummul Mukminin in the Muslimah study program. This research method uses a qualitative approach. The results of the research show that the DKM Ummul Mukminin's missionary communication planning for the Islamic Sciences study program has been implemented. However, the implementation of DKM Ummul Mukminin's da'wah communication was still not running optimally, because not all DKM administrators helped in carrying out Islamic studies, so only a few female students attended. Likewise, the aspect of evaluation and action to improve DKM Ummul Mukminin's da'wah communication in the Muslimah study program was only carried out once during the program so the results were less than optimal. Abstrak. Masjid Ummul Mukminin merupakan masjid yang berada di kawasan Universitas Islam Bandung. Masjid kampus memiliki peran yang sangat penting dalam kehidupan, melalui berbagai program dan kegiatan yang terstruktur, masjid kampus dapat menjadi wadah bagi mahasiswa untuk meningkatkan keimanan, seperti yang dilakukan di Masjid Ummul Mukminin melalui program kajian kemuslimahan. Namun, program kajian kemuslimahan tersebut belum banyak dihadiri oleh mahasiswi. Penelitian ini bertujuan untuk mengetahui bagaimana manajemen komunikasi dakwah DKM Ummul Mukminin dalam program kajian kemuslimahan, mulai dari perencanaan, pelaksanaan, evaluasi serta tindakan perbaikan DKM Ummul Mukminin dalam program kajian kemuslimahan. Metode penelitian ini menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa perencanaan komunikasi dakwah DKM Ummul Mukminin dalam program kajian kemuslimahan sudah dilakukan. Namun, dalam pelaksanaan komunikasi dakwah DKM Ummul Mukminin masih belum berjalan optimal, karena tidak semua pengurus DKM ikut membantu dalam pelaksanaan kajian kemuslimahan, sehingga mahasiswi yang hadir sedikit. Begitu juga pada aspek evaluasi serta tindakan perbaikan komunikasi dakwah DKM Ummul Mukminin dalam program kajian kemuslimahan ini hanya dilakukan sebanyak satu kali selama program berjalan, sehingga hasilnya tidak optimal.